Characterization of a plasma source for biomedical applications by electrical, optical, and chemical measurements. Issue 11 (19th September 2018) - Neretti, Gabriele; Tampieri, Francesco; Borghi, Carlo Angelo; Brun, Paola; Cavazzana, Roberto; Cordaro, Luigi; Marotta, Ester; Paradisi, Cristina; Seri, Paolo; Taglioli, Matteo; Zaniol, Barbara; Zuin, Matteo; et al.
Abstract : This paper reports the characterization of a low‐power, atmospheric pressure plasma source developed for and successfully tested in applications of plasma medicine. The source produces plasma by ionizing a helium flow containing traces of air. The effluent gas is thus enriched in reactive oxygen and nitrogen species as well as helium metastable excited states. Electrical measurements, Schlieren imaging, OES and various chemical analyses and probes enabled us to fully characterize the plasma source and to determine some fundamental parameters for treating living samples such as the power feeding the discharge, the optimal source to target distance, the maximum exposure time, and to identify the major chemical species responsible for the biological action on exposed living matter. Abstract : This paper reports the characterization of a low‐power, atmospheric pressure plasma source developed for and successfully tested in applications of plasma medicine. The source produces plasma by ionizing a helium flow containing traces of air. Electrical measurements, Schlieren imaging, OES, and various chemical analyses and probes enabled us to fully characterize the plasma source and to determine some fundamental parameters for treating living samples such as the power feeding the discharge, the optimal source to target distance, the maximum exposure time, and to identify the major chemical species responsible for the biological action on exposed living matter.